Supramolecular chemistry of helical foldamers at the solid–liquid interface: self-assembled monolayers and anion recognition. Issue 58 (1st July 2019) - Adam, Catherine; Faour, Lara; Bonnin, Valérie; Breton, Tony; Levillain, Eric; Sallé, Marc; Gautier, Christelle; Canevet, David
Abstract : Helical foldamers were incorporated in self-assembled monolayers that successfully transduce host–guest binding events. Abstract : The synthesis of a redox-active helical foldamer and its immobilization onto a gold electrode are described. These large molecular architectures are grafted in a reproducible manner and provide foldamer-based self-assembled monolayers displaying recognition properties.